Determinants of Psychology Students' Study Satisfaction. (March 2022) - Bebermeier, Sarah; Austerschmidt, Kim L.; Nussbeck, Fridtjof W.
Understanding characteristics that contribute to psychology students' academic success is important to better support them during their studies. Referring to person–environment fit theory, we examined effects of study-relevant characteristics (self-efficacy beliefs, self-assessed level of information about the study program) on subjective criteria of success (persistence with the choice of study subject, later study satisfaction) and controlled for effects of grade point average (GPA) and mathematical skills. We present a longitudinal survey study including five cohorts of first-year students (total N = 854). Mediation models ( N = 254) revealed that self-efficacy and level of information at study entry predicted students' persistence at the end of the first semester, which predicted satisfaction at the end of the second semester. In the presumed overall model we found total effects of self-efficacy and level of information, with direct and indirect effects (via persistence) on satisfaction, and no total or direct effects of GPA and mathematical skills, but an indirect effect of GPA on satisfaction. Thus, psychology students' satisfaction substantially depends on study-relevant characteristics and less on skills. An enhancement of students' self-efficacy beliefs and comprehensive information for those who are interested in the subject might help to increase satisfaction and thus success.